Pendidikan Nilai Spiritual dalam Prosesi Hijrah Nabi Muhammad SAW ke Madinah - Zulfatmi Zulfatmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This paper presents spiritual values and spiritual value education practices in the procession of the Prophet Muhammad's migration to Medina. These values are extracted from the Sirah Nabi text written in the book